Strategy For Improving Human Resources of Teachers and Staff at SMP Negeri 1 Dasuk, Sumenep Regency - Eka Yuniarti; Zahra Fitroh Amalia (Majapahit Journal of Islamic Finance and Management, 2026)
This study was motivated by the importance of human resource management in improving the quality of education in public junior high schools. The purpose of this study was to analyze the profiles, competencies, performance, obstacles, and human resource development strategies of teachers and educational staff at SMP Negeri 1 Dasuk, Sumenep Regency. This study used a qualitative approach with a descriptive-exploratory design. Data were collected through in-depth interviews, non-participatory observation, and documentation studies from ten informants, consisting of teachers and educational staff, then analyzed using the Miles and Huberman model. The results show that human resources administratively meet national standards, but competency development still faces limitations in terms of budget, time, and technological gaps. The leadership of the principal plays an important role in creating a collaborative work climate. Policy implications emphasize the need for strategic planning for human resource development based on needs and sustainability.